Konsep Pengembangan Kawasan Pariwisata sebagai Upaya Meningkatakan Promosi Pariwisata di Provinsi Aceh - Ashabul Yamin Asgha; Sophia Novita (Universitas Informatika dan Bisnis Indonesia, 2023)
Ethnic and cultural diversity as well as a large number of urban districts does not make Aceh Province devoid of tourist visits, both national and foreign tourists. Each year there is an increase in the number of tourists, and it interests the author to find out more about the concept developed by the Aceh provincial government in developing existing tourist areas to be able to optimize every tourism area to attract tourists. This study used a descriptive qualitative method, with data collection techniques by interview and literature study, interviews were conducted with the Head of the Communication Development and Marketing Strategy Section of the Aceh Culture and Tourism Office, Mr. M. Syahputra AZ, while a literature study done to add to the literature and data related to the research. This study found that the concept of developing a tourism area carried out by the Aceh Provincial Culture and Tourism Office is to divide the tourism area into three main areas, Area one includes Banda Aceh, Aceh Besar, and Sabang. The second area covers the central region, Aceh Tengah, Bener Meriah, and Gayo Lues, and the third area includes Simeulue and Singkil, where each area has its own tourist attraction.